UNLOCKING EFFECTIVE TEACHING: THE MEDIATING POWER OF INSTRUCTIONAL TECHNOLOGY SKILLS IN A SYSTEMATIC LITERATURE REVIEW - Ma, Widad; Che Mat, Azman; Ab Rahman, Ghazali Yusri; Muhammad, Anuar; Addhar, Nor Azizul (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The rapid evolution of educational technologies has brought attention to the critical role of instructional technology skills in enhancing teaching effectiveness. While the adoption of digital tools is widespread, understanding how these skills function as mediators in transforming teaching practices remains underexplored. This study aims to systematically review recent literature to examine the mediating role of instructional technology skills in effective teaching and learning environments. Employing the PRISMA framework, a systematic search was conducted across Scopus, Web of Science, and ERIC databases using defined inclusion criteria. From an initial pool of 1,019 studies, 22 empirical articles published between 2022 and 2024 were selected for thematic synthesis. The findings were organized into three major themes: (1) instructional technology as a mediator, (2) teacher competency, beliefs, and self-efficacy, and (3) organisational and contextual factors influencing technology integration. The results reveal that instructional technology skills significantly mediate the relationship between digital tool adoption and improved student learning outcomes. These skills enhance pedagogical strategies, support learner motivation, and foster collaborative, student-centered learning environments. Moreover, teacher self-efficacy and institutional leadership emerged as key factors in facilitating successful integration. Studies also highlighted that without adequate training, emotional readiness, and systemic support, the impact of technology remains limited. In conclusion, instructional technology skills serve as a dynamic bridge between digital innovation and effective pedagogical practice. Their mediating influence underscores the need for holistic professional development, strategic leadership, and institutional investment. This review offers valuable insights for educators, policymakers, and researchers aiming to leverage instructional technology for sustained educational improvement.